Melestarikan Budaya Damai Melalui Adat Bura Dame Pada Masyarakat Desa Lilimori - Anthonius Michael; Frumensia Ade Riska1; Hendrik Palimbo (BULLET : Jurnal Multidisiplin Ilmu, 2022)
Humans are the most noble creatures of God of all God's creatures. Humans have the rights that provide freedom to obtain protection and a sense of security from any kind of violence. With this human rights, violence in any form cannot be justified. The Sikka tribe is one of the tribes in Indonesia that has a peaceful tradition that descended from generation to generation. Peace tradition which are one of the efforts to prevent violence in the community called Bura Dame customs. The Bura Dame custom can provide a deterrent effect to the perpetrators of acts of violence for the sake of safety and peaceful life. The research method used in this study is a qualitative research using interviews. The custom of Bura Dame which contains anti-violence values has been lived by the Sikka tribe in Lilimori Village.